Wielkopolska w warunkach transformacji - diagnoza istniejącego stanu gospodarki - Chmielewski, Roman (Wydział Prawa i Administracji UAM, 1992)
The purpose of the article is to present the state of economy of Wielkopolska region in the light of the present adjustment processes, as well as to show inter-regional differences and threats in various spheres of social life. Wielkopolska region is meant here to include the area of fìve provinces: Kalisz, Konin, Leszno, Piła and Poznań. It is connected with the availability of statistical data, which in the case of some phenomena make it possible to present them in a more precise way than if particular provinces were the point of reference. The analysis refers to the period 1989 -1992.
Wielkopolska region in conditions of transformation - a diagnosis of the present economy